1988
DOI: 10.1128/jb.170.6.2841-2849.1988
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic characterization of osmoregulatory trehalose synthesis in Escherichia coli

Abstract: It has been shown previously that Escherichia coli accumulates endogenously synthesized trehalose under osmotic stress. We report here that E. coli contained an osmotically regulated trehalose-phosphate synthase which utilized UDP-glucose and glucose 6-phosphate as substrates. In the wild type, the synthase was induced by growth in glucose-mineral medium of elevated osmotic strength and the synthase itself was strongly stimulated by K+ and other monovalent cations. A laboratory strain which expressed the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
297
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(309 citation statements)
references
References 41 publications
8
297
3
1
Order By: Relevance
“…In cell extracts, the OtsA of P. freudenreichii was absolutely specific for ADP-glucose, a finding that appears to be unique as far as OtsA proteins are concerned. In fact, known OtsA proteins either can use the four glucosyl donors (Lapp et al, 1971;Killick, 1979;Pan et al, 2002;Silva et al, 2005), or are specific for UDP-or GDPglucose (Elbein, 1968;Giaever et al, 1988). Most surprising was the observation that the pure (native or recombinant) OtsA of P. freudenreichii lacked the absolute specificity shown in cell extracts, and recognized any of the four sugar-nucleotides as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In cell extracts, the OtsA of P. freudenreichii was absolutely specific for ADP-glucose, a finding that appears to be unique as far as OtsA proteins are concerned. In fact, known OtsA proteins either can use the four glucosyl donors (Lapp et al, 1971;Killick, 1979;Pan et al, 2002;Silva et al, 2005), or are specific for UDP-or GDPglucose (Elbein, 1968;Giaever et al, 1988). Most surprising was the observation that the pure (native or recombinant) OtsA of P. freudenreichii lacked the absolute specificity shown in cell extracts, and recognized any of the four sugar-nucleotides as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The genes related to a sugar-like carbon source were OtsA (trehalose-6-phosphate synthase), which utilizes glucose-6-phosphate as substrate (Gizver et al, 1988), UhpC (hexose phosphate utilization protein), which is a sensor for external glucose-6-phosphate) (Schwjppe et al, 2003), MetE (methyltetrahydropteroyltriglutamate-homocysteine S-methyltransferase), a vitamin B 12 -independent enzyme (Urbanowski and Stauffer, 1989), DsrA (putative anti-silencer RNA), a regulator of transcription to express RcsA promoter, which in its turn is responsible for capsular polysaccharide synthesis (Sledjeski and Gottesman, 1995), RseA (sigma-E factor regulatory protein), which is involved in the storage of sigma which is released during stress (Ades et al, 1999), SsaH and SsaM (putative effector proteins), both regulators of secretion of the type III secretion system (Lee et al, 2000) and SpaO, involved in surface presentation of antigens, secretory proteins. Other genes that were differentially expressed were related to specific limiting factors like iron (gene SitD) or anaerobic respiration (TtrA).…”
Section: Response Of S Enterica To Lettuce Root Exudatesmentioning
confidence: 99%
“…Third, in case of prolonged osmotic stress, E. coli can take up the osmoprotectants glycine betaine and proline from the environment via the proVWX-encoded ABC transporter or synthesize glycine betaine from the extracellular precursor choline 2,9,10 . Fourth, if no extracellular compatible solutes are available, E. coli induces expression of trehalose-6-phosphate synthase (OtsA) and phosphatase (OtsB) to produce high intracellular concentrations of the nonreducing disaccharide trehalose from the precursors UDP-glucose and glucose 6-phosphate, conveying long-term resistance to sustained osmotic stress [11][12][13] . Quantitative studies indicated, however, that the amounts of compatible solutes produced by E. coli may not be sufficient to maintain cell turgor exclusively based on increasing intracellular osmolality, implying accompanying effects such as molecular crowding 14 .…”
Section: Introductionmentioning
confidence: 99%